The ASEAN-5 future currency : maastricht criteria. - M., Azali; Wong, Kelly Kai Seng; Lee, Chin; Ahmad Nazar, Shafinaz (University Library of Munich, Germany, 2008)
In this recent decade, many of the economists and policymakers attempted to investigate the suitability of the East Asian region to form a currency union and based on the European countries experience as a benchmark. This study aims to investigate the long run real convergence in GDP per capita growth among Malaysia, Thailand, Singapore, Indonesia, and the Philippines, over 1978 to 2004. The Dickey Fuller (DF) and Augmented Dickey Fuller (ADF) unit root tests were conducted at first difference of GDP per capita for each country; the results demonstrated that all countries GDP per capita are stationary at first difference. The results of the Bound Testing Approach (Auto - Regression Distributed Lag (ARDL)) indicated that there is a long run relationship betwee variables in the Maastricht Criteria. The results showed that interest rate, inflation rate and the debt ratio experience that negative relationship to the GDP per capita. However, the exchange rate and surplus (or deficit) ratio shown the positive related to the GDP per capita. Therefore, the findings showed the ASEAN 5 countries have fulfilled the Maastricht Criteria with consistent to expected sign(s) except for Singapore’ exchange rate and Indonesia’s debt ratio. Hence, those ASEAN 5 countries in this study have potential to form a single currency.